UTILITY OF BRONCHOSCOPY WITH BRONCHOALVEOLAR LAVAGE AMONG HEMATOLOGIC TRANSPLANT RECIPIENTS IN THE ERA OF NON-INVASIVE TESTING - Feinstein, Marc B. (Respiration, 2021)
BACKGROUND: Pulmonary complications are common among hematologic stem cell transplant recipients. Their evaluation can be pursued through bronchoscopy with bronchoalveolar lavage (BAL) and a variety of available non-invasive studies, which include newer molecular markers for detecting a variety of infectious agents. OBJECTIVE: To evaluate the diagnostic yield of BAL among hematologic stem cell transplant (HSCT) patients relative to the yield of non-invasive testing. METHOD: Retrospective analysis of HSCT recipients who underwent both BAL and non-invasive testing at a cancer center in 2013 and 2014. RESULTS: There were 210 diagnostic results among 98 HSCT recipients. There were 84 unique findings on non-invasive testing that were not evident on BAL, and 36 unique findings on BAL that were not evident on non-invasive testing. Non-invasive testing tended to yield bacterial and viral infections more commonly, while BAL yielded mycobacterial isolates more commonly. CONCLUSION: While non-invasive testing and BAL are both helpful in this population, each appeared more precise than the other with individual lung diseases. Bronchoscopy with BAL and non-invasive testing should be considered complementary strategies in the workup of pulmonary complications among HSCT patients.